2009
DOI: 10.1186/1477-7827-7-75
|View full text |Cite
|
Sign up to set email alerts
|

Successful artificial insemination in the Asian elephant (Elephas maximus) using chilled and frozen-thawed semen

Abstract: Background: Artificial insemination (AI) using frozen-thawed semen is well established and routinely used for breeding in various mammalian species. However, there is no report of the birth of elephant calves following AI with frozen-thawed semen. The objective of the present study was to investigate the fertilizing ability of chilled and frozen-thawed semen in the Asian elephant following artificial insemination (AI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 21 publications
0
33
0
Order By: Relevance
“…The captive elephant population has also declined along with that of the wild elephants [22]. Thus, it is necessary to encourage breeding management and to maintain the pregnancy of captive Asian elephants in order to increase the population and maintain genetic diversity.…”
mentioning
confidence: 99%
“…The captive elephant population has also declined along with that of the wild elephants [22]. Thus, it is necessary to encourage breeding management and to maintain the pregnancy of captive Asian elephants in order to increase the population and maintain genetic diversity.…”
mentioning
confidence: 99%
“…These may, in part, explain why the absolute levels of post-thaw semen quality in this study were low, despite using general techniques that had yielded better mean results in a previous study (Thongtip et al, 2009). Differences in post-thaw semen quality between males and between ejaculates from a specific male have been reported for many species (Neild et al, 2003;Garde et al, 2008;Lopes et al, 2009;Dorado et al, 2010).…”
Section: Discussionmentioning
confidence: 70%
“…Although captive populations have been established and maintained, they are not currently considered sustainable due to a combination of factors, including the risk of inbreeding within the geographically isolated populations, low fertility, unbalanced sex ratios and high infant mortality. Artificial insemination (AI) techniques have been developed in an attempt to facilitate genetic management (Saragusty et al, 2009;Thongtip et al, 2009), and are relatively successful when using fresh or chilled semen (Schmitt et al, 2001). In addition, African elephant semen has been cryopreserved successfully, and this encouraged attempts to cryopreserve Asian elephant semen using the same extenders.…”
Section: Introductionmentioning
confidence: 99%
“…Adv., 10 (12): 903-910, 2015 significantly different (p>0.05). In two cases, there were positive reactions between blood samples from breeding pairs that resulted in the abortion of two fetuses at 17 months of gestation without evidence of infectious disease or poor management (1 calf from Thongtip et al, 2009; 1 calf from unpublished data).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, passage of a heavy fetus through the vagina can cause the placenta to detach from the endometrium by severing the narrow maternal placental hilus, which then leads to intrauterine hemorrhage (Allen et al, 2003). Still births, especially late term and neonatal death are significant problems of captive elephants in western zoos (Saragusty et al, 2009) and have also been observed in Thailand (Thongtip et al, 2009;unpublished data). It is not known, if reactions to blood incompatibility between the fetus and elephant mother are causes of these problems, but given the non sustainability of most captive elephant populations, it is imperative to understand causes of poor reproductive success.…”
Section: Introductionmentioning
confidence: 99%